Pengaruh CHSE (Cleanliness, Health, Safety, Environment Sustainability) dan Hotel Facility terhadap Customer Satisfaction di Hotel Augusta Garut - Fahmy Septiadi; Sabilla Saberina; Aggi Panigoro; Theresia Manalu (LPPM UNIBI, 2023)
This study aims to determine the effect of CHSE (Cleanliness, Health, Safety, Environment Sustainability) and Hotel Facility on Customer Satisfaction at Hotel Augusta Garut. This is motivated by the development of the Hospitality Tourism Industry in West Java, as well as the many bad reviews or negative reviews from guests who have stayed at Hotel Augusta Garut and give unfavorable ratings on hotel booking applications such as Agoda, Traveloka, and others. The data in this study were collected by distributing questionnaires to the respondents. The population in this study is tourist visits staying in Garut Regency seen from the total tourist visits from 2019 – 2023 as many as 345,363 visitors. The number of samples taken is based on calculations using the Taro Yamane formula with a total sample of 100 (onehundred) respondents. The results of distributing questionnaires were analyzed using multiple regression analysis, coefficient of determination, t-test and F-test. The results showed that: (1) there was a positive and significant influence between CHSE partially on Customer Satisfaction in Hotel Augusta Garut (2) there is a positive and significant influence between Hotel Facility partially on Customer Satisfaction at Hotel Augusta Garut (3) there is a positive and significant influence between CHSE and Hotel Facility simultaneously on Customer Satisfaction at Hotel Augusta Garut.